2017
DOI: 10.1074/jbc.r117.797399
|View full text |Cite
|
Sign up to set email alerts
|

At the confluence of ribosomally synthesized peptide modification and radical S-adenosylmethionine (SAM) enzymology

Abstract: Radical S-adenosylmethionine (RS) enzymology has emerged as a major biochemical strategy for the homolytic cleavage of unactivated C-H bonds. At the same time, the post-translational modification of ribosomally synthesized peptides is a rapidly expanding area of investigation. We discuss the functional cross-section of these two disciplines, highlighting the recently uncovered importance of protein-protein interactions, especially between the peptide substrate and its chaperone, which functions either as a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
(66 reference statements)
0
23
0
Order By: Relevance
“…The role of reduced iron as the electron donor in many reactions, including photosynthesis, and oxidized iron as the universal terminal electron acceptor in respiratory chains, as well as the catalytic propensities of iron as a key cofactor for a variety of enzymatic reactions determined its irreplaceable functions in all living organisms [3][4][5][6][7]. The newly emerging field of radical enzymology points to a possibly important role of iron in primordial hydrogen abstraction reactions occurring anaerobically in primitive organism through tightly coordinated alkyl radical driven mechanisms [8]. The essential high chemical reactivity of iron also imposed the creation of highly specialized, complex mechanisms of competition for iron between host cells and invading bacterial pathogens [1], along with those for transport and control of extra-and intra-cellular iron, based on tight binding of this metal by specialized proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The role of reduced iron as the electron donor in many reactions, including photosynthesis, and oxidized iron as the universal terminal electron acceptor in respiratory chains, as well as the catalytic propensities of iron as a key cofactor for a variety of enzymatic reactions determined its irreplaceable functions in all living organisms [3][4][5][6][7]. The newly emerging field of radical enzymology points to a possibly important role of iron in primordial hydrogen abstraction reactions occurring anaerobically in primitive organism through tightly coordinated alkyl radical driven mechanisms [8]. The essential high chemical reactivity of iron also imposed the creation of highly specialized, complex mechanisms of competition for iron between host cells and invading bacterial pathogens [1], along with those for transport and control of extra-and intra-cellular iron, based on tight binding of this metal by specialized proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant importance of PQQ to human health, the details of the biosynthetic pathway of this molecule have been, until recently, largely unknown. Recent studies by our group revealed that a key step in the PQQ biosynthesis involves the formation of a C–C bond between two amino acids in the peptide substrate PqqA, catalyzed by the radical SAM enzyme PqqE in complex with the chaperone PqqD (Barr et al, 2016; Latham, Barr, & Klinman, 2017; Latham et al, 2015). This reaction is both complicated and fascinating not only because it is an O 2 -sensitive reaction occurring in an aerobic bacteria ( Mex ) but also due to the fact that it requires precise redox control and interaction among multiprotein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that MftC belongs to a RS enzyme subfamily that contains an elongated C-terminal domain annotated as a SPASM domain (Subtilosin A, Pyrroloquinoline quinone, Anaerobic Sulfatase maturating enzyme, and Mycofactocin) (Haft and Basu 2011). The proteins associated with the RS-SPASM subfamily are known peptide modifiers that have been shown to catalyze intramolecular C-S bonds and C-C bonds and oxidative decarboxylation reactions on the precursor peptide (Flühe et al 2012;Flühe et al 2013;Wieckowski et al 2015;Barr et al 2016;Khaliullin et al 2016;Khaliullin et al 2017a;Latham et al 2017a;Schramma and Seyedsayamdost 2017). Using the MftC clade as a starting point, Haft identified the remaining five mft genes in the immediate neighborhood localized around mftC (Figure 1).…”
Section: Architecture and Occurrence Of The Mycofactocin Biosyntheticmentioning
confidence: 99%
“…In both cases, the first step requires the RS enzymes PqqE and MftC, respectively. Both enzymes catalyze carbon-carbon bond formation between an sp 2 and an sp 3 hybridized carbon on their precursor peptides, in the presence of an accessory RRE domain (PqqD and MftB, respectively), resulting in a chemically crosslinked peptide (Latham et al 2015;Barr et al 2016;Khaliullin et al 2016;Khaliullin et al 2017a;Latham et al 2017a). However, while PqqE catalyzes the carboncarbon bond formation between glutamate and tyrosine on its precursor peptide PqqA in a single step (Figure 3), MftC catalyzes a two-step modification of the precursor peptide MftA (Figure 4) (Barr et al 2016;Khaliullin et al 2017a).…”
Section: Mycofactocin Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation